Development of Learning Videos for Simple Chemistry Practicum with Acid-Base based on Green Chemistry Topic for Students of Class XI - Yupita Tri Rezeki; Agus Kamaludin* (Universitas Syiah Kuala, 2023)
Practicum is critical for students to develop their abilities and comprehension of the subject being studied. The lack of a laboratory and a laboratory assistant, as well as limited instruments and practicum materials, are the primary reasons why practicum activities are not performed in schools. Therefore, the use of instruments and materials which are available in everyday life can be an alternative to keep carrying the practicum out. This study aimed to develop a simple chemistry practicum video on green chemistry- based acid-base solutions and determine the quality of the developed video. The research method employed was development research (R D) which adapted the 4-D models (define, design, development, and disseminate), although it was limited to the stage of development in this study. The research instruments used were the product quality assessment sheets for material expert, media expert, reviewers (senior high school chemistry teachers), and student response sheets. The developed product was a video containing determining the best indicators, making pH routes, determining the pH of acid-base, and acid-base titrations. A quality assessment on the product by material expert was 95% with the very good category; from media expert, it got a percentage of 95% with the very good category; and from reviewers, a percentage of 95% with the very good category was obtained. Furthermore, based on student responses to the product, a percentage of 98% with a very good response category was also obtained. Based on the results, the developed product was appropriate to be used as an alternative media to replace acid-base chemistry practicum in schools